Sensory rhodopsin II from the haloalkaliphilic natronobacterium pharaonis: light-activated proton transfer reactions. - Schmies, G (2000)
In the present work the light-activated proton transfer reactions of sensory rhodopsin II from Natronobacterium pharaonis (pSRII) and those of the channel-mutants D75N-pSRII and F86D-pSRII are investigated using flash photolysis and black lipid membrane (BLM) techniques. Whereas the photocycle of the F86D-pSRII mutant is quite similar to that of the wild-type protein, the photocycle of D75N-pSRII consists of only two intermediates. The addition of external proton donors such as azide, or in the case of F86D-pSRII, imidazole, accelerates the reprotonation of the Schiff base, but not the turnover. The electrical measurements prove that pSRII and F86D-pSRII can function as outwardly directed proton pumps, whereas the mutation in the extracellular channel (D75N-pSRII) leads to an inwardly directed transient current. The almost negligible size of the photostationary current is explained by the long-lasting photocycle of about a second. Although the M decay, but not the photocycle turnover, of pSRII and F86D-pSRII is accelerated by the addition of azide, the photostationary current is considerably increased. It is discussed that in a two-photon process a late intermediate (N- and/or O-like species) is photoconverted back to the original resting state; thereby the long photocycle is cut short, giving rise to the large increase of the photostationary current. The results presented in this work indicate that the function to generate ion gradients across membranes is a general property of archaeal rhodopsins.